A dandelion wish - Thorpe, Kiki; Christy, Jana (New York : Random House, 2013)
"Mia and her friends have discovered a magical passageway to Never Land! But when her little sister Gabby goes to Never Land alone, the passageway closes up, with a fairy stuck on the Main Land side, too"--
"A Stepping Stone book."
RL: 3.1.
Keywords: Never-Never Land (Imaginary place) -- Juvenile fiction; Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Missing children -- Juvenile fiction; Fantasy fiction